Infancy weight gain and neurodevelopmental outcomes among term-born infants at age one year: A large prospective cohort study in China. Issue 4 (19th May 2022) - Lu, Min-Shan; Lu, Jin-Hua; Zhang, Li-Fang; Liu, Xian; Zhao, Xuan; Nagraj, Shobhana; Shen, Song-Ying; Xiao, Wan-Qing; He, Jian-Rong; Qiu, Xiu
ABSTRACT: To investigate the association between infancy weight gain and neurodevelopment among term-born infants. Singleton term-born infants (n = 5837) were included from the Born in Guangzhou Cohort Study. Absolute weight gain was obtained by calculating the weight difference from birth to exactly 12 months. The primary outcome was neurodevelopment at age one year, which included five developmental domains. Global developmental delay was defined as delays in ≥3 domains. Multivariable logistic regression was used to examine the associations between infancy weight gain and neurodevelopment. Compared with infants gaining 6001–7000 g (reference group), infants gaining ≤5000 g had higher odds of delay in adaptive, gross motor, fine motor, social, and global developmental delay, infants gaining 5001–6000 g had higher odds of gross motor delay and social delay. A sex-stratified analysis showed that compared with the reference group, gaining ≤5000 g was associated with higher odds of fine motor delay in male infants, while gaining >7000 g was associated with higher odds of fine motor delay in females. Inadequate infancy weight gain is associated with higher odds of poor neurodevelopment at age one year among term-born infants.